2020
DOI: 10.1007/s00234-020-02581-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebral arteriovenous shunts: a comparison of parallel imaging time-of-flight magnetic resonance angiography (TOF-MRA) and compressed sensing TOF-MRA to digital subtraction angiography

Abstract: Purpose Time-of-flight (TOF)-MR angiography (MRA) is an important imaging sequence for the surveillance and analysis of cerebral arteriovenous shunt (AVS), including arteriovenous malformation (AVM) and arteriovenous fistula (AVF). However, this technique has the disadvantage of a relatively long scan time. The aim of this study was to compare diagnostic accuracy between compressed sensing (CS)-TOF and conventional parallel imaging (PI)-TOF-MRA for detecting and characterizing AVS. Methods This study was appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Our findings are in agreement with previous studies which showed comparable results between CS TOF and PI TOF MRA in the detection of a variety of cerebrovascular pathologies, including aneurysms, stenosis and arteriovenous shunts [21][22][23][24][25]. In particular, no significant differences were found between CS TOF and PI TOF MRA in the depiction of intact aneurysms, as well as in the measurement of neck, height and width of aneurysms [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in agreement with previous studies which showed comparable results between CS TOF and PI TOF MRA in the detection of a variety of cerebrovascular pathologies, including aneurysms, stenosis and arteriovenous shunts [21][22][23][24][25]. In particular, no significant differences were found between CS TOF and PI TOF MRA in the depiction of intact aneurysms, as well as in the measurement of neck, height and width of aneurysms [22].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed that CS TOF MRA has comparable sensitivity and specificity to PI TOF MRA in the detection of a variety of cerebrovascular pathologies, including aneurysms, stenosis and arteriovenous shunts, while allowing a 2-to 3-fold reduction in scan time [21][22][23][24][25]. However, no data are available on the diagnostic accuracy of CS TOF MRA in the follow-up of endovascularly treated aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of hemorrhage is associated with deep venous drainage, and deep and infratentorial brain location [ 79 ], and demographically children and females [ 80 ]. TOF-MRA with wide coverage like a whole brain MRA is necessary to evaluate feeders and nidus of AVM [ 81 ]. CE-MRA or MR-DSA is also performed for evaluation of brain MRA [ 82 ].…”
Section: Clinical Application Of Vw-mri—arterial Diseasesmentioning
confidence: 99%
“…However, recent technical advances have addressed this trade‐off. One example is compressed sensing TOF‐MRA, which capitalizes on the mathematical “sparsity” of information (vessels vs. background), thus enabling accurate diagnosis of arteriovenous (AV) shunting with a sequence time of 2.5 minutes 19 …”
Section: Time‐of‐flight Magnetic Resonance Angiographymentioning
confidence: 99%